The man who quit money - Sundeen, Mark, 1970- (New York : Riverhead Books, 2012)
"In the first year of the twenty-first century, a man standing by a highway in the middle of America pulled from his pocket his life savings - thirty dollars -laid it inside a phone booth, and walked away. He was thirty-nine years old, came from a good family, and had been to college. He was not mentally ill, nor an addict. His decision appears to have been an act of free will by a competent adult. in the twelve years since, as the Dow Jones skyrocketed to its all-time high, Daniel Suelo has not earned, received, or spent a single dollar." De boodschap van Sundeen is duidelijk: denk eens na over je leven, beslis eens wat voor jou het belangrijkste is, ban de dingen die je niet nodig hebt. Voor alle duidelijkheid: Daniel Suelo is geen fictief personage, bestaat echt en heeft inderdaad het geld af gezworen.
Keywords: Suelo, Daniel, -- 1961-.; Alternative lifestyles -- United States; Money -- Social aspects; Self-reliant living -- United States; Simplicity